Implementasi Model Pembelajaran Cooperative Learning Tipe Jigsaw dalam Meningkatkan Aktivitas dan Hasil Belajar Matematika - Maryati, Tutik; Sujiono, Sujiono; Purnomo, Danang Try; Sudarto, Sudarto; Shadikah, Arina Afiyati; Harto, Sugik; Rispatiningsih, Dwi Maryani (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The aim of this research is to determine the increase in students' Mathematics learning activities and outcomes by implementing the Jigsaw type cooperative learning model in class XI IPA.1 of SMA Negeri 1 Ampel for the 2021/2022 academic year. The research was carried out in the even semester of the 2021/2022 academic year for 2 months, namely from April to May 2022. The data collection method in this research used the test method and observation method. Data collection tools include test items, observation guidelines, and test results sheets. The research results are presented as follows: (1) Implementation of the Jigsaw type cooperative learning model can increase the mathematics learning activities of class XI IPA.1 students at SMA Negeri 1 Ampel for the 2021/2022 academic year. The student activity score in cycle I was 6.86 (fair), cycle II was 7.43 (good) and cycle III was 8.29. (2) Implementation of the Jigsaw type cooperative learning model can improve the mathematics learning outcomes of class XI IPA.1 students at SMA Negeri 1 Ampel for the 2021/2022 academic year. The number of students who achieved the KKM score in cycle I to cycle III was 18 people or 95%. Apart from that, the average class score in cycle I was 73.46; in cycle II was 74.62; and in cycle III it was 77.31.